Twisting in improving processing of waste-derived yarn into high-performance reinforced composite. (1st October 2021) - Yu, Xichen; Fan, Wei; Azwar, Elfina; Ge, Shengbo; Xia, Changlei; Sun, Yanli; Gao, Xingzhong; Yang, Xue; Wang, Shujuan; Lam, Su Shiung
Abstract: Waste cotton fibers was spun into yarns for potential use as high performance composites in order to recycle the ever-increasing waste textiles generation and solve the disposal problem. This study investigates the effects of different twist levels (550–1050 TPM), twist ratios (0.1–0.5 plied yarn twist to single yarn twist), and epoxy resin impregnation rates (0.2–1.0 cm/s) on tensile properties of single yarns, plied yarns, and yarn reinforced composites derived from waste cotton fibers. The detection of the failure mechanisms of the examined yarns was confirmed via SEM analysis and images captured by high-speed camera. The twist factor at low twist level (550 TPM), twist ratio (0.1) and impregnation rate (0.3 cm/s) were determined as optimum twist factors to produce plied yarn-reinforced composite with high tensile strength of 286 MPa. The optimum twist of single yarn reinforced composites was 0.76 times the optimum twist of the single yarn alone. Twisting significantly influenced the manufacturing of high-performance composites from waste-derived yarn. The obtained results provide a new paradigm for high value utilization of waste textile through conversion into high-performance composites. Highlights: Twisting is applied to processing of waste-derived yarn over various twist factors. Different twist level, twist ratio and epoxy resin impregnation rate are examined. Reinforced composites of high tensile strength are made at optimum twist. Yarn reinforced composites have 0.76 times optimum twist than the clothing yarn. Impregnation rate greatly affects tensile strength of the reinforced composite.